Hybrid cardiovascular sourced extracellular matrix scaffolds as possible platforms for vascular tissue engineering. Issue 3 (1st August 2019) - Reid, James A.; Callanan, Anthony
Abstract: The aim when designing a scaffold is to provide a supportive microenvironment for the native cells, which is generally achieved by structurally and biochemically imitating the native tissue. Decellularized extracellular matrix (ECM) possesses the mechanical and biochemical cues designed to promote native cell survival. However, when decellularized and reprocessed, the ECM loses its cell supporting mechanical integrity and architecture. Herein, we propose dissolving the ECM into a polymer/solvent solution and electrospinning it into a fibrous sheet, thus harnessing the biochemical cues from the ECM and the mechanical integrity of the polymer. Bovine aorta and myocardium were selected as ECM sources. Decellularization was achieved using sodium dodecyl sulfate (SDS), and the ECM was combined with polycaprolactone and hexafluoro‐2‐propanol for electrospinning. The scaffolds were seeded with human umbilical vein endothelial cells (HUVECs). The study found that the inclusion of aorta ECM increased the scaffold's wettability and subsequently lead to increased HUVEC adherence and proliferation. Interestingly, the inclusion of myocardium ECM had no effect on wettability or cell viability. Furthermore, gene expression and mechanical changes were noted with the addition of ECM. The results from this study show the vast potential of electrospun ECM/polymer bioscaffolds and their use in tissue engineering.